2017
DOI: 10.2337/db17-0595
|View full text |Cite
|
Sign up to set email alerts
|

MondoA Is an Essential Glucose-Responsive Transcription Factor in Human Pancreatic β-Cells

Abstract: Although the mechanisms by which glucose regulates insulin secretion from pancreatic β-cells are now well described, the way glucose modulates gene expression in such cells needs more understanding. Here, we demonstrate that MondoA, but not its paralog carbohydrate-responsive element-binding protein, is the predominant glucose-responsive transcription factor in human pancreatic β-EndoC-βH1 cells and in human islets. In high-glucose conditions, MondoA shuttles to the nucleus where it is required for the inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…To further investigate the function of the GABA B receptor in ECN90, we searched for genes whose induction by forskolin would be blunted upon pretreatment with baclofen (16 h, 100 µM). Forskolin treatment induced a robust increase in MAFA, PCSK1, PAX4, IGFBP3 and the non-coding long RNA Linc00473, as previously shown in our microarray analyses from forskolin treated human EndoC-βH1 cells 20 . This induction was blunted upon pretreatment with baclofen ( Fig.…”
Section: Ecn90 Expresses Both Subunits Of the Metabotropic Gaba B Recsupporting
confidence: 86%
“…To further investigate the function of the GABA B receptor in ECN90, we searched for genes whose induction by forskolin would be blunted upon pretreatment with baclofen (16 h, 100 µM). Forskolin treatment induced a robust increase in MAFA, PCSK1, PAX4, IGFBP3 and the non-coding long RNA Linc00473, as previously shown in our microarray analyses from forskolin treated human EndoC-βH1 cells 20 . This induction was blunted upon pretreatment with baclofen ( Fig.…”
Section: Ecn90 Expresses Both Subunits Of the Metabotropic Gaba B Recsupporting
confidence: 86%
“…the deleterious effects of combined elevated glucose and NEFA concentrations, prompted us to study EndoC-βH1 cell viability following both high glucose and NEFA exposure. The efficiency of HG (30 mmol/l) treatment was validated by TXNIP mRNA upregulation ( [39] and data not shown). Remarkably, we did not observe cell toxicity after palmitate incubation at low glucose (5.6 mmol/l) or HG ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have reported a close relationship between glucose metabolism and MA. [ 30 ] Accordingly, MLXIP play a role in gene regulation in response to cellular glucose levels; [ 31 ] C1QTNF12 regulates glucose metabolism in liver and adipose tissues; [ 32 ] and CREM is associated with Type 1 diabetes mellitus. [ 33 ] For FGR, C FGR‐A (Table S10, Supporting Information) included CD63 , which is involved in different levels of platelet activation in preeclamptic, normotensive pregnant, and non‐pregnant women.…”
Section: Discussionmentioning
confidence: 99%